Mortality attributable to fine particulate matter in Asia, 2000–2015: a cross-sectional cause-of-death analysis - Vladimir Canudas-Romo; Pattheera Somboonsin (BMJ Open)
Objectives To investigate the effect that particulate matter with a diameter of 2.5 μg (PM2.5) had on mortality in Asian populations in years 2000–2015.Setting Mortality and level of PM2.5 data from the United Nations, Global Burden of Disease and University of Chicago were used.Outcome measures Age pattern of mortality and the number of life-years lost (LYL) attributable to PM2.5 in years 2000–2015. LYL were further separated into causes of death to quantify the contribution of each cause.Results Ischaemic heart disease (IHD) mortality increased to represent over 31% of the LYL attributable to PM2.5 between 2005–2010 and 2010–2015 in Asia (females 31% and males 35%). However, great diversity in LYL attributable to PM2.5 by causes-of-death were found across the region, with IHD proportions of LYL ranging from 25% to 63% for males from Eastern and Central Asia, respectively. Similar diversity was observed for mortality attributable to PM2.5 for other causes of death across Asia: chronic obstructive pulmonary disease (LYL ranging from 6% to 28%), lung cancer (4% to 20%) and stroke (11% to 22%).Conclusion PM2.5 is a crucial component in the rising health effects in Asia. The diverse trends in cause-specific mortality attributable to PM2.5 creates a further challenge for health systems in the region. These findings highlight that immediate interventions are needed to mitigate the increasing levels of air pollution and with that reduce its detrimental effect on the health and mortality of Asian populations.